(3GdJMaI GdHgjI aj WHbGJ GdTGaYjIs - (3YHO Gddg Hf MLGRj Hf EHQGgje GdTQbGhj GdCRgQj,J (B1227 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi SGhi ai GdaVd eOGO GdYdeGA HOeGA GdTgOGA deG JYdbJ GdCeGd HPcQ JQGLe HYV GdTGaYjI GdPjf hLOhG ai GdCYUGQ GdeJCNQI s
(3BNQgG (B:s
(3hcGf GdaQGZ ef JShjOg jhe GdKdGKGA GdeHGQc dJSY eVjf ef TgQ QLH GdaQO ef TghQSfI dEMOi hYTQjf HYO GdeGFJjf hGdCda ef GdgLQI GdfHhjI WjHkG eHGQckG Bejf Bejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B263 - (3U(B491s
(3GfXQ HQbe (B149 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B41s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B480 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B729 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B96 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs